Improvement of Hygiene and Sanitation in Fish Traders Group of Kedonganan Fish Market Toward Healthy Market: Peningkatan Hygiene dan Sanitasi pada Kelompok Pedagang Ikan di Pasar Ikan Kedonganan Menuju Pasar Sehat - Pande Ayu Naya Kasih Permatananda; I Gde Suranaya Pandit; Putu Nita Cahyawati (Yayasan Ahmar Cendekia Indonesia, 2022)
Most traditional markets in Indonesia do not meet the Healthy Market requirements as stipulated in the Ministry of Health Regulation No. 17 of 2020, including the Kedonganan Fish Market in Badung Regency, Bali. The solutions and methods offered in this program include hygiene and sanitation counseling, demonstrations and hand washing exercises, as well as training on making economical ice packs. Partners will also receive PPE assistance packages, personal hygiene, and environmental sanitation to help partners implement the program. In terms of input, this activity was successfully carried out on July 2, 2022, with satisfying enthusiasm from the participants and very cooperative partners. For utcome, there is a significant increase in partner knowledge. In the output indicators, there is a significant change in partner attitudes and all partners have been able to carry out the 7 steps of hand washing. This program is expected to be implemented continuously in order to realize a Healthy Market. Abstrak Sebagian besar pasar tradisional di Indonesia tidak memenuhi syarat Pasar Sehat sebagaimana Peraturan Kementerian Kesehatan no 17 tahun 2020, termasuk Pasar Ikan Kedonganan yang berada di Kabupaten Badung, Bali. Solusi dan metode yang ditawarkan pada program ini meliputi penyuluhan hygiene dan sanitasi, demonstrasi dan senam cuci tangan, serta pelatihan pembuatan ice pack ekonomis. Mitra juga akan mendapatkan paket bantuan APD, hygiene personal, dan sanitasi lingkungan untuk membantu mitra menerapkan program. Secara input, kegiatan ini berhasil terlaksana dengan baik pada tanggal 2 Juli Juli 2022 dengan antuasiasme peserta yang memuaskan dan mitra sangat koperatif. Secara outcome, terdapat peningkatan pengetahuan mitra yang bermakna signifikan. Pada indikator output, terdapat perubahan sikap mitra yang bermakna signifikan dan seluruh mitra sudah mampu melaksanakan 7 langkah cuci tangan. Program ini diharapkan dapat dilaksanakan berkelanjutan untuk dapat mewujudkan Pasar Sehat.